Influence of sewage sludge composts with straw or ash on oribatid mites (Acari, Oribatida) from pine forest litter in laboratory conditions - Klimek, Andrzej; Chachaj, Bogusław; Kosakowski, Leszek (Biological Letters, 2011)
In a substrate obtained from municipal sewage sludge composts, the C:N ratio was decreased during the 12-month experiment. The amount of forest litter (layer 1 or 2 cm thick), used for fauna introduction, did not influence significantly the mean abundance of oribatid mites in sewage sludge compost. Oribatid mites tolerated compost alone or with straw, but were negatively influenced by addition of wood-ash. Abundance of oribatid mites in compost alone was increased from the 3rd month, and its maximum occurred in the 10th month. Abundance of oribatid mites in compost with straw was clearly increased since the 10th-12th month of the experiment. Generally the abundance of oribatid mites was mainly affected by Ramusella mihelcici, which was most abundant in compost alone and with straw (maximum abundance was above 100 000 individuals · m-2). However, species diversity of the mites was very low at the end of the experiment.